2018
DOI: 10.22201/fesi.20071523e.2018.2.487
|View full text |Cite
|
Sign up to set email alerts
|

Measuring eating habits and physical activity in children: Synthesis of information using indexes and clusters / Medición de hábitos saludables y no saludables en niños: Síntesis de la información utilizando indicadores y conglomerados

Abstract: Assessing healthy habits related to child overweight and obesity is important concerning the prevention efforts. A variety of measures to assess eating habits and physical activity are available, being the self-report frequency questionnaires the most common and cost-efficient. Nevertheless, those questionnaires generate a large amount of data. Considering this, the purpose of the study was to develop a proposal to synthesize information from the Child Overweight/Obesity Healthy related Habits Questionnaire (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Finally, two programmes with a strategy for nutrition and PA at the school level encourage a balanced diet and the development of school PA programmes. 73 91 More details are in table 3 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, two programmes with a strategy for nutrition and PA at the school level encourage a balanced diet and the development of school PA programmes. 73 91 More details are in table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, five studies were identified by cross-referencing. Finally, 70 scientific articles were included 52–124. All these document and articles were related to 13 initiatives on physical and social environmental modifications, 7 in the area of PA and 6 with a nutrition focus (online supplemental files 2; 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, Varela Arévalo et al [53] identified two HLH profiles in Colombian schoolchildren aged eight to twelve years based on their dietary habits, digital entertainment consumption, and physical activity. A first cluster was characterized by low physical activity, while the second cluster grouped children with high digital entertainment consumption [53].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple sociodemographic aspects, such as income level, gender and age of the child, and area of residence can have a significant effect on healthy living habits. Children from disadvantaged schools and lower-income families tend to have unhealthy eating habits compared to children from high-income schools and families [5,36,38,[52][53][54][55]. Likewise, children who grow up with one or neither parent tend to report fewer positive attitudes toward healthy habits, as well as behaviors such as smoking, drug use, violence, low physical exercise, and diet of poor nutritional quality compared to those who grow up under the care of both parents [56].…”
Section: Introductionmentioning
confidence: 99%